Independent factors associated with bicycle helmet use in a Korean population: A cross-sectional study. (19th May 2018) - Son, Sun Han; Oh, Sang Ho; Kang, Si Hyun; Kim, Don-Kyu; Seo, Kyung Mook; Lee, Shi-Uk; Lee, Sang Yoon
ABSTRACT: Objective : Although identification of factors that influence helmet use during bicycle riding is necessary for the selection of groups that require safe cycling education, limited baseline data are available. The aim of the present study was to analyze the rate of helmet use and the demographic factors that were independently associated with helmet use among Korean bicycle riders. Methods : In this cross-sectional study, we used public data from the Sixth Korean National Health and Nutrition Examination Survey conducted in 2013 and 2014. Helmet users were defined as subjects who always, usually, or frequently wore helmets when cycling. Independent factors associated with helmet use were determined using odds ratios (ORss) adjusted for 5 demographic factors via multivariate logistic regression analysis. Results : In the total population, 4, 103 individuals were bicycle riders; among these, 782 individuals (19.1%) wore helmets. A total of 21.1% of male riders used helmets, compared to 15.5% of female riders ( P <.001). The adjusted logistic regression model revealed that female sex (OR = 0.665; 95% confidence interval [CI], 0.554–0.797), teenage status (OR = 0.475, 95% CI, 0.333–0.678), and low household income (OR = 0.657, 95% CI 0.513–0.841) were significantly associated with nonuse of helmets. Conclusions : Female sex, teenage status, and low household income were independent factors associated with the nonuse of helmets. We identified factors associated with helmet use during bicycle riding through analysis of baseline data on helmet usage.